MULTILEVEL RESEARCH OF INNOVATIVE AND REPRODUCTION DEVELOPMENT OF REGIONS ON THE BASIS OF THE STATISTICAL ANALYSIS - Yu. A. Dmitriev; D. Yu. Fraymovich; Z. V. Mishchenko (Финансы: теория и практика)
The analysis of the approaches to an assessment of innovative development of territories which are available today allows to establish the fact of possibility of their improvement and entering of essentially new non-standard procedures into algorithms of calculation of resultant sizes. Thus as important difference of the developed technique comparison of the indicators received at the exit across various territories on the basis of their statistical group by the principle of the maximum similarity, and also the characteristic of the reached parameters against actually available dynamics in a temporary cut can act. The modified multilevel method of calculation of the indicators characterizing extent of use of innovative and reproduction capacity of regional systems is presented in article. Analyses are applied regression and cluster statistical. This results from the fact that all subjects have different «starting» opportunities, de facto various financing, and also institutional, political and legal, climatic, ecological and other conditions. Therefore the offered multilevel research allows to formulate certain conclusions concerning efficiency of attraction of regional innovative and reproduction, scientific and technological, intellectual and other resources of each separately taken region for modernization implementation. The nomenclature of the factors included in model can be corrected during improvement and improvement. Universal character of the considered technique allows to vary the list of the estimated parameters,proceeding from information opportunities,object of research,and also qualification of the involved analysts. The offered mechanism of calculation can be actual for research institutes, and also regional authorities at justification of administrative and legal decisions within implementation of effective programs of social and economic development.